COMMUNITY BASED TOURISM PERUBAHAN PERILAKU EKONOMI MASYARAKAT SEBAGAI DAMPAK PENGEMBANGAN PARIWISATA ALAM PERDESAAN : STUDI KASUS PEMANDU WISATA AIR TERJUN NYARAI KECAMATAN LUBUK ALUNG, PROVINSI SUMATERA BARAT - Yudha Yudha Rahman (Journal of Science and Applicative Technology, 2017)
Special Interest Tourism is an alternative for experiency tourist attraction based on particular motivation and interest of the travelers different from attractions. The problem that has been persisty is that the local community of Gamaran Salibutan Village cutting trees and damaging nature in Gamaran Protected Forest which carry out potential and natural tourist attractions. This study analyze the change of society’s economic behaviour as an effect of rural nature tourism development. The method used Qualitative research with case study approach. The analysis showed that the presence of tourism development of Nyarai Waterfall has positive benefits for the economy of the local community, namely the increase of people's income and their job opportunities as a tour guide for woodcutter the unemployed youth and the women are able to open a stall so that possibly in adding to the family income.